The Correlation of Work Patterns, Physical Activity, and Physiological Factors with Well-Being in Female Workers - Betania Jumponi Hastuti; Heny Setyawati (Universitas Negeri Semarang, 2026)
This study investigates the complex relationship between work patterns, physical activity, and physiological indicators specifically resting heart rate and blood pressure with the psychological well-being of female office workers at Tritunggal Christian School Semarang. Given the high administrative demands often faced by female workers, this research utilized a quantitative approach with a total sampling method (N=78). Well-being was measured using the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), and data were analyzed through Spearman's Rank correlation. The statistical results revealed that all null hypotheses were accepted (p > 0.05): Work Pattern (p=0.290; ρ=-0.150), Physical Activity (p=0.697; ρ=0.045), Resting Heart Rate (p=0.783; ρ=0.031), and Blood Pressure (p=0.661; ρ=0.045). These findings suggest that physiological and behavioral factors are not direct predictors of well-being in this specific community. The lack of significance is largely attributed to the